Alaskan Quest: Summer of the Midnight Sun - Book 1 - Peterson, Tracie (Minneapolis, Minn. : Bethany House, 2006)
"The Barringer family is happy in the Alaskan Territory. Confronted by an old flame, Leah realizes her feelings never went away and she is whisked away on an unforgettable journey"--Provided by publisher.
Keywords: Alaska -- Fiction; Romance fiction; Domestic fiction; Christian fiction